Analysis of Criminogenic Factors in Drug Abuse Behavior in Children (Case Study at Makassar Police Headquarters) - Sapada, Andi Tenri; Mappaselleng, Nur Fadhilah; Fitri, Ainul (Journal of Public Representative and Society Provision, 2025)
This study aims to determine the factors that influence the occurrence of criminology against narcotics crimes committed by children and the efforts of investigators against narcotics abuse crimes committed by children in the city of Makassar. This study uses an empirical research method. The location of the study was at the Satres Narcotics Police Resort of South Sulawesi City. The types and sources of data are primary data and secondary data obtained from field data in the form of (interview results) and then data analysis was carried out. The results of this study indicate, What factors cause narcotics crimes committed by children in the Makassar Police area. What efforts are made by law enforcement officers in overcoming narcotics crimes committed by children in the Makassar Police area. The recommendation of this study is that it is very necessary to improve the quality of personnel in training, especially regarding narcotics abuse and it is hoped that the general public will be more careful in taking steps and being careful with their relationships.